PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN MAHASISWI FAKULTAS EKONOMI DAN BISNIS ISLAM DALAM MEMBELI PRODUK KOSMETIK - Jannah, Raudatul; Mardini, Yulida; Al-Mubarak, M. Adi Riswan; Zaini, Ahmad (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2022)
Against the background of women's need for cosmetic and skin care products which are increasing and not infrequently, cosmetics are a primary need in every woman's monthly shopping. Therefore, with the increasing number of existing cosmetics. So cosmetic companies must be able to compete how to create a new innovation that can provide satisfaction for cosmetic users so that consumers can make their choices. In making these decisions, consumers will be influenced by product quality and price. Based on research results. Simultaneously there is a significant influence between product quality and price on purchasing decisions. This is obtained from the value of Fcount = 76.088 > Ftable = 2.40 with a significance value (˂0.01) less than α = 0.1 or a significance of 10%. While partially the product quality and price variables also have a significant effect on purchasing decisions. It is known that the product quality variable has a value of Tcount = 3.052 > Ttable = 1.674 with a significance value of 0.04 ˂ 0.1 Then H1 is accepted and H0 is rejected, meaning that there is a partial influence between the product quality variable (X1) on the purchase decision variable (Y). while the price variable has a Tcount = 4,449 > Ttable 1.674 with a significance value (˂0.01) less than 0.1. So it can be concluded that H1 is accepted and H0 is rejected, meaning that there is a partial influence between the price variable (X2) on the purchase decision (Y).